(untitled) (Actualizaciones en Sida e Infectología, 2019)
Psoas-iliac muscle abscess is considered a rarity, the use of images such as computed tomography or magnetic resonance imaging has improved its detection. This study reviews cases of psoas-iliac abscess in hospitalized patients between July 2015 and February 2018 in a hospital in CABA, Argentina. In one of the patients the origin was considered primary ,while in the other eight it was secondary. There was a predominance of collections associated with spondylodiscitis. The most frequent symptom was fever. Staphylococcus aureus was the most frequent organism obtained in microbiological samples. A high level of suspicion must be held in the presence of fever, lumbar pain and sometimes alteration of the gait. The use of broad spectrum antibiotics in addition to evacuation of collections is the most effective strategy.